Numerical analysis termal fluid in a heat exchanger with baffles inclination - Ahmed Youcef; Rachid Saim; Mohammed Chokri Kourti; Mohammed Benhamou (Revue des Énergies Renouvelables, 2022)
A research on Thermo-hydraulic performance carried out on three types of heat exchanger with different baffles inclination 15°, 25°, 45° by the computer code Fluent, the model achievable is turbulence . The results show big recirculation zones and lower temperature peaks on the outlet for the decreased angles, the average heat transfer coefficient decreased by 1 %, pressure loss decreased by 1.2%, amount of heat exchanged between the tubes and the water increases by 1.2%.